Application of New Iterative Method to Time Fractional Whitham–Broer–Kaup Equations - Nawaz, Rashid; Kumam, Poom; Farid, Samreen; Shutaywi, Meshal; Shah, Zahir; Deebani, Wejdan (Frontiers in Physics, 2020)
This article presents the fractional Laplace transform with the help of new iterative method (NIM) is extended for an estimated solution of coupled system of fractional order PDEs. The time fractional Whitham–Broer–Kaup system is taken as a test example where derivatives are given in the Caputo sense. Numerical results found by the proposed method are compared with that of ADM, VIM, and OHAM. Numerical consequences display that the proposed method is reliable and operative for solution of fractional order coupled system of PDEs. The proposed method shows better accuracy in even two iterations compared to the methods given above.